2008
DOI: 10.1002/cne.21616
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic acetylcholine receptors in macaque V1 are most frequently expressed by parvalbumin‐immunoreactive neurons

Abstract: Acetylcholine (ACh) is believed to underlie mechanisms of arousal and attention in mammals. ACh also has a demonstrated functional effect in visual cortex that is both diverse and profound. We have reported previously that cholinergic modulation in V1 of the macaque monkey is strongly targeted toward GABAergic interneurons. Here we examine the localization of m1 and m2 muscarinic receptor subtypes across subpopulations of GABAergic interneurons-identified by their expression of the calcium-binding proteins par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
118
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(145 citation statements)
references
References 101 publications
25
118
1
Order By: Relevance
“…8B). Consistent with this, mAChR proteins (m1 and m2) have been observed in cells throughout cortical layers in macaque V1 (Disney and Aoki 2008;Disney et al 2006;Mrzljak et al 1993), suggesting that m1-and m2-AChRs play important roles in facilitatory modulation. It remains to be clarified, however, how this facilitatory effect is mediated by mAChRs in the neuronal circuitry of V1.…”
Section: Facilitatory Ach Effect In V1supporting
confidence: 69%
See 2 more Smart Citations
“…8B). Consistent with this, mAChR proteins (m1 and m2) have been observed in cells throughout cortical layers in macaque V1 (Disney and Aoki 2008;Disney et al 2006;Mrzljak et al 1993), suggesting that m1-and m2-AChRs play important roles in facilitatory modulation. It remains to be clarified, however, how this facilitatory effect is mediated by mAChRs in the neuronal circuitry of V1.…”
Section: Facilitatory Ach Effect In V1supporting
confidence: 69%
“…8B; n ϭ 47). An antagonistic effect by At was observed across all cortical layers, which is consistent with the expression of mAChR proteins (Disney and Aoki 2008;Disney et al 2006). We estimated laminar differences in the relative contribution of non-mAChRs by calculating their mean percentage contribution in each layer.…”
Section: Receptor Subtypes Mediating the Facilitatory Ach Effectsupporting
confidence: 57%
See 1 more Smart Citation
“…In fact, it has been observed that spiking reliability in the LGN is also enhanced following BF electrical stimulation (Goard and Dan 2009). However, this effect could also be mediated by V1 infragranular layer neurons, which express mAChR (Disney and Aoki 2008;Disney et al 2006) and are the main source of LGN top-down modulatory inputs (Fitzpatrick et al 1994). It thus remains possible that the LGN effects are a consequence and not the cause of V1 reliability modulations following BF stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The presynaptic M2 receptors are located on the axons of symmetric synapses, in keeping with their role as autoreceptors [12]. However, M2 receptors are also present in a subset of glutamatergic synapses and GABAergic interneurons [13]; nearly a third of cortical GABAergic neurons express M2 receptors [14].…”
Section: Muscarinic Receptorsmentioning
confidence: 96%